Panel4: Health Narratives, Communities and Global Health - Hu, Jiaqi (The Journal of Medicine, Humanity and Media, 2023)
Session 4 of the 6th International Conference on “Medicine, Humanity, and Media” (MHM 2023): Health Communication under Digitization, convened at the School of Journalism and Communication of Peking University on November 4, 2023. With the theme “Health Narratives, Communities and Global Health”, the session was moderated by Jiang Yizhen (Associate Professor from the School of Public Health at Xiamen University), with Li Zhenyi (Director of the School of Communication and Culture at Royal Roads University, Canada) and Zhang Zhan (Assistant Professor from the School of Humanities and Social Sciences at University of Nottingham Ningbo China) as commentators. The session featured six speakers who delivered thought-provoking paper presentations, showcasing the deep integration of diverse health communication topics and profound humanistic care in the age of globalization.